Identifying Contractorsâ Planned Quality Costs in Indonesian Construction Projects - Puti F. Marzuki; M. Wisridani (Journal of Engineering and Technological Sciences, 2014)
In  a very competitive construction industry, quality costs have to be measured  to  be  able  to  identify  potential  quality  problem  areas  and  to  focus attention  on  work  output  improvement  opportunities.  The  awareness  of contractors on the importance of quality costs could be reflected in the extent of their  quality  costs  planning.  This  paper  presents  an  identification  of  planned quality  costs  in  three  construction  projects  executed  by  two  large  Indonesian contractors,  a  state-owned  company  and  a  private  company  in  Jakarta.  The objective is to enable the contractors to elaborate their quality costs planning and thereby improve their work output based on the findi ngs. Quality  costs  are  first grouped into  three  categories: prevention, appraisal,  and  failure  costs.  Based on the  works  of  previous  researchers,  a  list  of  quality  management  activities  that should be covered in each quality costs category is then created. The contractors' planned quality costs data  for each category are  identified and  collected through interviews  and  questionnaire  surveys  that   refer  to  the  list.  Quality  costs  are expressed  as  a  percentage  of  contract  value.  It  is  revealed  that  although  large contractors  already  have  certain  knowledge  on  quality  costs  in  construction projects,  these costs are  not planned in a structured way  through an analysis of systematic  quality  costs  records.  Through  cost  categorization  it  is  also  shown that higher prevention and appraisal costs lead to lower failure costs.  It is then concluded  that  a  lot  of  work  is  still  to  be  done  by  the  contractors  to  set  up  a quality  costs  recording  system  which  can  serve  as  a  basis  for  their  quality improvement planning.